2015
DOI: 10.1002/ps.4014
|View full text |Cite
|
Sign up to set email alerts
|

Spray distribution evaluation of different settings of a hand-held-trolley sprayer used in greenhouse tomato crops

Abstract: Air assistance and flat-fan nozzles allow volume rates to be reduced while maintaining or improving spray quality distribution. The working parameters of hand-held sprayers must be considered to reduce environmental risk and increase the efficacy of the spraying process. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
(55 reference statements)
1
19
0
3
Order By: Relevance
“…For the cucumber crop, the depositions on the internal leaves in the middle and bottom of the canopy were 17 and 37% higher for the AAE sprayer than for the BP sprayer, respectively. These results are in concordance with those obtained by Llop et al ., who concluded that a sprayer equipped with air assistance improved the depositions on leaves and increased penetrability into the canopy.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…For the cucumber crop, the depositions on the internal leaves in the middle and bottom of the canopy were 17 and 37% higher for the AAE sprayer than for the BP sprayer, respectively. These results are in concordance with those obtained by Llop et al ., who concluded that a sprayer equipped with air assistance improved the depositions on leaves and increased penetrability into the canopy.…”
Section: Resultssupporting
confidence: 93%
“…and Cho et al ., about 30 to 35% of yield losses can be prevented by applications of pesticides. However, because of the limitations of the greenhouse's structure and operational space, pest management in greenhouses is a challenge, and handheld and knapsack sprayers are still widely used . In China and many other developing countries, the PPPs are normally sprayed using low‐technology manual systems, which are difficult to regulate as the spray quality depends mainly on the skill of the operator .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a higher spray volume also improved the coverage and effect of run-off. Llop et al 27 found that air assistance and flat-fan nozzles allowed a reduction in volume from 1000 to 600 L ha −1 while maintaining or improving spray quality distribution with a hand-held-trolley sprayer in greenhouse-cultivated tomato. Studies have also indicated that spray volume affects not only the deposition and distribution, but also the control efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to techniques using water-sensitive papers, other methods imply the use of fluorescent tracers. We can mention the work of Llop et al [15] in which the use of a fluorescent tracer (Helios SC 500; 0.1% v/v ) traced the deposition on the leaves of the plants (in ng per cm 2 ) as well as the coverage rate of the leaves by the sprayed product. In Reference [16], the authors tried to correlate the surface coverage rate and droplet size distribution.…”
Section: Introductionmentioning
confidence: 99%